Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Mata Pelajaran Matematika pada Materi Vektor Melalui Model Pembelajaran Jigsaw di Kelas XII IPA 1 MA Negeri 3 Banjarmasin Tahun Pelajaran 2016/2017 - Abdurrachman, Abdurrachman Abdurrachman (Jurnal PTK dan Pendidikan, 2018)
This research aims to increase the activity and the results of students' mathematics learning on Vector material by using Jigsaw model in class XII IPA 1 MAN 3 Banjarmasin. Type of Research is Classroom Action Research. Data collection techniques using test techniques and non-test techniques. The analysis technique used is descriptive quantitative and qualitative descriptive. The result is student activity by using JIGSAW model activity enough 15 students (40,54%) and student activity good category 22 student (59,46%). Student Activity In Cycle II of 37 students who categorized good activity as much as 6 students (16.22%) and who categorized very good activity as much 31 students (83,78%). Student learning result with Vector Material materials using JIGSAW model Cycle I from 37 students who do not complete 15 students (40,54%) decreased to 5 students (13,51%) while 22 students complete (59,46%) on cycle I increased in cycle II of complete student as much as 32 student (86,49%).